Intraoperative Protective Mechanical Ventilation for Prevention of Postoperative Pulmonary Complications: A Comprehensive Review of the Role of Tidal Volume, Positive End-expiratory Pressure, and Lung Recruitment Maneuvers. (September 2015) - Güldner, Andreas; Kiss, Thomas; Serpa Neto, Ary; Hemmes, Sabrine N. T.; Canet, Jaume; Spieth, Peter M.; Rocco, Patricia R. M.; Schultz, Marcus J.; Pelosi, Paolo; Gama de Abreu, Marcelo
Abstract : Postoperative pulmonary complications are associated with increased morbidity, length of hospital stay, and mortality after major surgery. Intraoperative lung-protective mechanical ventilation has the potential to reduce the incidence of postoperative pulmonary complications. This review discusses the relevant literature on definition and methods to predict the occurrence of postoperative pulmonary complication, the pathophysiology of ventilator-induced lung injury with emphasis on the noninjured lung, and protective ventilation strategies, including the respective roles of tidal volumes, positive end-expiratory pressure, and recruitment maneuvers. The authors propose an algorithm for protective intraoperative mechanical ventilation based on evidence from recent randomized controlled trials. Abstract : Postoperative pulmonary complications increase morbidity and mortality, but can be reduced by lung-protective mechanical ventilation. Different strategies using low tidal volumes, positive end-expiratory pressure, recruitment maneuvers, and a combination of these have been suggested, but only a few of them are based on evidence. This review proposes an algorithm for protective intraoperative mechanical ventilation that builds on utmost recent randomized clinical trials.